Reliability Analysis of Bearing Capacity of Shallow Foundation on c- φ Soil - Acharya, Mahesh; Acharya, Indra Prasad (Journal of Advanced College of Engineering and Management, 2019)
Bearing capacity of shallow foundation is a challenging problem for geotechnical engineers. The difficulty comes from multiple sources of uncertainty. Only the uncertainties in Soil properties; unit weight (γ), cohesion(c), and angle of friction (φ) are taken in this study. The Reliability Based Design method is used for the assessment of bearing capacity of shallow foundation by First-and second-order approximation using Taylor’s series expansion and Mathcad Computer program which provide systematic analysis of uncertainties and allow the designer how reliable are their designs. The Terzaghi Bearing capacity equation is used for the analysis along with the certain range of variability (CV %) associated with the variables. For the reliability analysis, to become more realistic two real cases of shallow foundation on c-φ soil has been taken as a sample case.